Lego Star Wars : the visual dictionary - Beecroft, Simon (London ; New York : DK, 2009)
A visual dictionary that provides information on the spaceships, vehicles, creatures, equipment, and minifigures that are part of the LEGO Star Wars sets.
May include Lego minifigure.
WARNING: CHOKING HAZARD - Small parts. Not for children under 3 yrs.
6.2
3-6
Keywords: Models and modelmaking -- Juvenile literature; LEGO toys -- Juvenile literature; Star Wars films -- Juvenile literature; Models and modelmaking; LEGO toys; Star Wars films; Models and modelmaking; LEGO toys; Star Wars films; LEGO toys; Models and modelmaking; Star Wars films; Toys -- Pictorial works